Takereana, a new genus of Idoteidae (Crustacea: Isopoda: Valvifera) from New Zealand - Poore, Gary C. B.; Hurley, Desmond E. (Zootaxa, 2015)
Takereana n. gen. is erected for the New Zealand species, Idotea festiva Chilton, 1885, which is redescribed. Takereana, Austridotea Poore, 2001 and Idotea Fabricius, 1798 are the only idoteid genera in which both pleonites 1 and 2 are truly articulating. In all other genera of Idoteidae pleonite 2 is variously fused to pleonite 1 and visible only laterally. The new genus differs from Austridotea in that maxillipedal palp articles 2–3 and 4–5 are fused and operculate whereas in Austridotea the palp is of five free articles or has only articles 4–5 fused. All species of Austridotea are smooth with laterally expanded coxae, a quite different habitus from ornamented Takereana festiva. Takereana differs from Idotea in having two uropodal rami rather than one, greater fusion of maxillipedal palp articles, lacking spiniform setae on the pereopods, and unusual narrow pleopods 1. Takereana has an obsolete setose mandibular molar while it is columnar and toothed in both these genera.